Curriculum Management in Improving The Quality of Student Learning and Academic Achievement - Neliwati Neliwati; Uswatun Hasanah; Retno Pringadi; Akhmad Sirojuddin; Muhamad Arif (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This research was conducted in relation to curriculum management in improving the quality of learning and academic achievement of students at MAS Insan Kesuma Madani in Namorambe. This research will use a qualitative method, namely the research is carried out in natural conditions (natural setting). The data sources for the nature of this research are divided into two groups, namely primary data sources and secondary data sources. The data collection technique that will be carried out is triangulation. From the findings in the field, that the curriculum planning process carried out in madrasas is in accordance with management theory, which starts from planning, implementation, and final results which will be closely related to the evaluation process of what is carried out from beginning to end. Improving discipline and improving the quality of human resources and Mas insan Kesuma Madani in Namorambe have carried out several curriculum implementation programs to improve the quality of learning and student academic achievement.